Flexible Pension Take-up in Social Security - Yvonne Adema; Jan Bonenkamp; Lex Meijdam (Tinbergen Institute, 2013)
This paper studies the redistribution and welfare effects of increasing the flexibility of individual pension take-up. We use an overlapping-generations model with Beveridgean pay-as-you-go pensions, where individuals differ in ability and life span. We find that introducing flexible pension take-up can induce a Pareto improvement when the initial pension scheme contains within-cohort redistribution and induces early retirement. Such a Pareto-improving reform entails the application of uniform actuarial adjustment of pension entitlements based on average life expectancy. Introducing actuarial non-neutrality that stimulates later retirement further improves such a flexibility reform.
urn:NBN:nl:ui:15-1765/40959
Keywords: H55; H23; J26; 330; redistribution; retirement; flexible pensions; Flexible Altersgrenze; Rentenreform; Wohlfahrtsanalyse; Umlageverfahren; Pareto-Optimum; Overlapping Generations; Theorie